2012
DOI: 10.1007/s10529-012-0852-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of sex-linked SCAR markers in dioecious Hippophae rhamnoides L. (Elaeagnaceae)

Abstract: The actinorhizal plant seabuckthorn (Hippophae rhamnoides L., Elaeagnaceae) is a wind pollinated dioecious crop. To distinguish male genotypes from female genotypes early in the vegetative growth phase, we have developed robust PCR-based marker(s). DNA bulk samples from 20 male and 20 female plants each were screened with 60 RAPD primers. Two primers, OPA-04 and OPT-06 consistently amplified female-specific (FS) polymorphic fragments of 1,164 and 868 bp, respectively, that were absent in the male samples. DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 24 publications
0
15
1
Order By: Relevance
“…Contrary to earlier reports (e.g., Singh 2003;Korekar et al 2012, Raina et al 2012, the natural populations of seabuckthorn from western Himalaya investigated in the present study were found to be subdioecious. The populations were comprised of a mixture of strictly unisexual and PGM plants; the proportion of latter ranged from~2 to 4%.…”
Section: Subdioecy In Seabuckthorncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to earlier reports (e.g., Singh 2003;Korekar et al 2012, Raina et al 2012, the natural populations of seabuckthorn from western Himalaya investigated in the present study were found to be subdioecious. The populations were comprised of a mixture of strictly unisexual and PGM plants; the proportion of latter ranged from~2 to 4%.…”
Section: Subdioecy In Seabuckthorncontrasting
confidence: 99%
“…This high similarity observed between male and female genomes suggests a recent/ongoing evolution of dioecy in seabuckthorn. Earlier studies, based on their attempts to isolate gender-specific SCAR markers, have also suggested high homology between the genomes of male and female plants in H. rhamnoides (Persson and Nybom 1998;Sheng et al 2006;Sun et al 2006;Sharma et al 2010;Korekar et al 2012;Das et al 2017). These studies were based on limited efforts using markers like RAPD, SSR etc., and emphasized the need to generate a large number of markers to understand the extent of similarity between male and female genomes.…”
Section: Limited Differences Between Male and Female Genomesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, sex-specific SCAR markers were developed in seabuckthorn. The studies of Korekar et al [7] reported for the first time two robust sex-linked SCAR markers, namely HrX1 and HrX2. The RAPD-SCAR patterns authenticated large sets of 120 female plants and rejected 100 male plants.…”
Section: Applications Of Scar Markermentioning
confidence: 99%
“…SCAR markers have proven their utility in detection of Fusarium oxysporium f. sp. ciceris and cubense [4] [5], selection of hybrid strains of Saccharomyces cerevisiae [6], validation of sex of plants in early stage [7] and identification of powdery mildew resistance genes [8]. The several potential applications that are put together by earlier workers are well summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%